Adolescents in social-educative measures and mental health: an integrative review - Picolli, Ana Clara Gomes; Arruda, Daniel Péricles (Argumentum, 2023)
Adolescents in social-educative measures and mental health: an integrative reviewThis study aims to understand and analyse national scientific publications between 2001 and 2021 that address the mental health of adolescents who are serving open or closed social-educational measures in Brazil. We conducted an integrative literature review of 2,381 records held on the databases of SciELO, PubMed, Portal BVS, and Portal de Periódicos CAPES/MEC. After establishing inclusion and exclusion criteria, fourteen articles were selected for analysis, divided into three axes of analysis: pathologisation and/or medicalisation; perception of professionals/institutions; and stressful events, risk, and protection factors. The analysis revealed excessive medicalisation and psychiatric diagnosis of adolescents serving a custodial socio-educational measure, and the barriers these adolescents face in accessing mental health services. It also revealed life pathways marked by violence and lack of social protection, with a high incidence of risk factors and absence of protective factors.